Cutaneus T-Cell Lymphoma in 53 Years Old Woman: Histopathological Features - Ivani, Ivani; Murasmita, Alamanda; Mawardi, Prasetyadi; Oktavriana, Triasari (Journal La Medihealtico, 2024)
Cutaneous T-cell lymphomas (CTCLs) are clinically heterogeneous T-cell lymphomas that arise in the skin and are characterized by their clinical and pathological features. The pathogenesis of CTCL is not fully understood. The incidence of CTCL increases significantly with age, with a median age at diagnosis at about 55 years of age and a four-fold increase in incidence appreciated in patients over 70. A 53 year old woman presented with complaints of reddish spots and lumps on her left forearm and back which spread to her chest, stomach and legs. On examination, a lump the size of a golf ball was found on the left forearm and back as well as reddish spots that felt itchy and painful. Histopathological examination with HE staining showed proliferation of lymphoid follicles without a germinal center and monotonous cells of small to medium size partially surrounding the tubular glands in the dermis layer. Immunohistochemical examination revealed positive for CD 45 as well as CD 3 and negative for CD 20. A case of CTCL has been reported in a 53-year-old woman. Histopathological examination and immunohistochemistry are important to diagnose this disease.